Implementing Team-Based Innovation in Primary Health Care in British Columbia - Alexandra Lukey; Karin Maiwald; Paul Wankah; Mylaine Breton; Peter Hirschkorn; Nelly D. Oelke (McMaster University Library Press, 2022)
Improving health services integration for patients with complex needs is a national priority in Canada. Health systems in all provinces grapple with the rising complexity of patients and the services they need. Team-based primary health care (PHC) models have been implemented in diverse ways to improve patients' experiences, increase the coordination of care, improve population health and reduce costs. While some provinces have more than two decades of experience with PHC teams, others such as British Colombia (BC) have made changes more recently. We conducted an in-depth analysis of 12 provincial policy documents produced since 2011 to study the evolution of interprofessional models in PHC. BC has integrated team-based care through overarching policy support and funding from the provincial government. Structural practice changes to support team-based care, such as Primary Care Networks (PCNs), were designed to address the quadruple aim, a framework designed to improve health system performance through integrated primary care. Policies have addressed the vision and goals of team-based care, but discussion of processes that support teams, such as a strategy for capitation-based funding and team composition, were non-specific. Finally, there is a significant need for a provincial strategy for continuous quality improvement and evaluation of reforms.